2019
DOI: 10.1038/s41598-019-48057-9
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter-attributable mortality and relationships with carbon dioxide in 250 urban areas worldwide

Abstract: Urban air pollution is high on global health and sustainability agendas, but information is limited on associated city-level disease burdens. We estimated fine particulate matter (PM 2.5 ) mortality in the 250 most populous cities worldwide using PM 2.5 concentrations, population, disease rates, and concentration-response relationships from the Global Burden of Disease 2016 Study. Only 8% of these cities had population-weighted mean concentrations below the World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 17 publications
2
56
1
Order By: Relevance
“…The NASA HAQAST Indicators Tiger Team facilitated the transfer of global-scale satellite remote sensing and related data to stakeholders for tracking the world's progress toward mitigating air pollution and climate change. By the end of the year-long Tiger Team, population wildfire exposure had been incorporated into the latest Lancet Countdown report (Watts et al, 2019), the GBD Study and the State of Global Air are incorporating the new ozone concentrations (Chang et al, 2019;GBD 2017Risk Factor Collaborators, 2018 and are considering integrating the new NO 2 concentrations and asthma burdens (Achakulwisut et al, 2019), and the Climate and Clean Air Coalition and C40 Cities are using urban PM 2.5 mortality burdens (Anenberg et al, 2019) to inform city planning for air pollution and climate change mitigation. The Lancet Countdown is also incorporating our wildfire and green space estimates in future iterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NASA HAQAST Indicators Tiger Team facilitated the transfer of global-scale satellite remote sensing and related data to stakeholders for tracking the world's progress toward mitigating air pollution and climate change. By the end of the year-long Tiger Team, population wildfire exposure had been incorporated into the latest Lancet Countdown report (Watts et al, 2019), the GBD Study and the State of Global Air are incorporating the new ozone concentrations (Chang et al, 2019;GBD 2017Risk Factor Collaborators, 2018 and are considering integrating the new NO 2 concentrations and asthma burdens (Achakulwisut et al, 2019), and the Climate and Clean Air Coalition and C40 Cities are using urban PM 2.5 mortality burdens (Anenberg et al, 2019) to inform city planning for air pollution and climate change mitigation. The Lancet Countdown is also incorporating our wildfire and green space estimates in future iterations.…”
Section: Discussionmentioning
confidence: 99%
“…City-level PM 2.5 mortality burden 10.1029/2020GH000270 GeoHealth estimates are increasingly of interest, as populations are growing in many cities where air quality is also worsening (United Nations, 2014;World Health Organization, 2016a). We therefore developed the first estimates of urban PM 2.5 mortality burdens for 250 cities worldwide, using methods that were consistent globally and compatible with the GBD Study (Anenberg et al, 2019). Our estimates were enabled by years of research that preceded our study to generate high-quality gridded (0.1°× 0.1°) estimates of surface PM 2.5 concentrations globally by integrating AOD observations from multiple satellites with global chemical transport models and ground observations (Shaddick et al, 2018;van Donkelaar et al, 2016).…”
Section: Urban Pm 25 Mortality Burdensmentioning
confidence: 99%
“…Cities in LMICs are most impacted by air pollution due to concentrated poverty, rapid industrialization, a lack of environmental regulations, and often limited enforcement of existing regulations. Urban air pollution in LMIC cities is up to 17 times higher than in Europe and North America [30,31], and many residents are additionally exposed to indoor and neighborhood air pollution from household solid fuel burning [30,32]. Exposure to PM 2.5 from solid fuel stoves is higher than that to outdoor PM 2.5 in most high-income countries [33], yet there is substantial overlap between indoor (solid fuel) and urban PM 2.5 exposures in LMICs.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Similar findings are also shown in China's Clean Air Action, which successfully reduced major air pollutants from 2010 to 2017, but as accompanied by 16% increases in CO 2 emissions 30 . Another study found that wealthier cities in North America have reduced their PM 2.5 concentrations and mortality burdens considerably in recent years, while their CO 2 emissions have not declined in parallel 31 . This largely one-way co-benefit pathway is because of differences in the major actions for controlling CO 2 versus other pollutant emissions 16 .…”
Section: Discussionmentioning
confidence: 99%